Biological pathways and networks implicated in psychiatric disorders. (April 2015) - Sullivan, Patrick F; Posthuma, Danielle
Highlights: We review 42 studies that tested biological pathways in five major psychiatric disorders. For schizophrenia and bipolar disorder current sample sizes are largest and pathway results tend to converge. Consensus pathways supported by empirical studies and carefully vetted by experts are needed. Future pathway analyses need carefully developed software, large sample sizes, and replication. Abstract : Psychiatric disorders are polygenic traits, influenced by multiple genes largely of small individual impact on risk. Recent studies indicate that these genes are not randomly distributed but cluster into functionally connected biological pathways. We review the recent literature on genome-wide common and rare variants that implicate biological pathways for five major psychiatric disorders. For schizophrenia (SCZ) and bipolar disorder (BD), there is converging evidence from multiple studies that implicate similar biological pathways, while for other psychiatric disorders converging evidence is lacking. We conclude that larger datasets as well as improved definition of pathways are required to enable the replicable identification of biological pathways underlying psychiatric disorders, which will be crucial in defining novel targets for future pharmaceutical interventions.